Hegel: A Dialetheist? Truth and Contradiction in Hegel's Logic. Issue 2 (August 2019) - Bordignon, Michela
Abstract: The article aims to show that Priest wrongly associates Hegel's dialectic with his dialetheism. Even if Priest correctly argues that the notion of contradiction in Hegel's logic is a logical one and that contradiction is meant to be true, Hegel goes a long way beyond Priest's dialetheism insofar as he is not committed to a dialetheist conception of a three truth-values logic. I start my analysis with a brief introductory overview of the dialetheist's thesis of the truth of contradiction. Then, in the first part of the article, I show that Hegel's notion of contradiction can be equated with a logical contradiction and that Hegel argues that some contradictions are true. In the second part of the paper I show that Hegel's thesis of the truth of contradiction is different from Priest's, because Hegel endorses a developmental conception of truth which allows him to account for complex and dynamic properties of reality in a way that Priest's does not allow.